LANGUAGE FEATURES OF THE GENRES OF OFFICIAL BUSINESS STYLE - Khadjimuratova, Ugiloy (Журнал иностранных языков и лингвистики, 2021)
Official-business style stands out among other book styles with its stability, closure and standardized. Despite the large variety of business documents, their language strictly obeys the requirements of official-business presentation: the accuracy of the formulation of legal norms and the need for absolute adequacy of their understanding, the composition of the mandatory elements of the design of the document providing its legal rule of law, the standardized nature of the presentation, the stable form of the location of the material in a certain logical sequences